ANALISIS TINGKAT KEBISINGAN DAN INTENSITAS PENCAHAYAAN PADA RUANG KELAS SMP NEGERI 25 MALANG TERHADAP KENYAMANAN BELAJAR - Cantika Purna Ardhis Syahfirna; Sutrisno; Chesta Nahda Tigaprilarda; Chillie Aurora Meydiano; Clara Devina Rizki Alfreda; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The physical learning environment, particularly lighting and noise levels, plays an important role in supporting students' comfort and concentration during the learning process. Inadequate lighting can cause eye fatigue and reduce learning focus, while high noise levels can interfere with communication and concentration during classroom activities. This study aims to measure lighting intensity and noise levels in classrooms and the library at SMP Negeri 25 Malang, and to analyze their compliance with learning environment comfort standards. The method used in this study was direct measurement using an environment tester. Lighting measurements were conducted at several points in classrooms and the library at different times, while noise measurements were carried out at certain time intervals to obtain average values. The results showed that the average lighting intensity in classrooms was approximately ±90 lux and in the library ±68 lux, where both values were still below the recommended lighting standards of 250–300 lux for classrooms and 300 lux for libraries. Meanwhile, the average noise level in classrooms was approximately ±75 dB, which exceeded the recommended learning comfort limit of about 55 dB, while the noise level in the library was ±52 dB and still within acceptable limits. Based on these results, it can be concluded that the lighting conditions in classrooms and the library have not met the recommended comfort standards, and the noise level in classrooms is still relatively high, indicating the need for improvements to enhance the comfort of the learning environment.